Systematic, biogeographic and microhabitat-based morphometric variation of the bivalve Anomalocardia squamosa (Bivalvia: Veneridae: Chioninae) in Thailand - Roopnarine, Peter D. (2008)
The venerid genus Anomalocardia is tropical American in origin, yet has a distribution spanning the tropical western Atlantic to western Pacifi c oceans. This distribution makes it the most widespread genus of the monophyletic, tropical American Chioninae. Other tropical American chionine genera have either remained restricted to American waters since their originations at various times during the early Neogene, or have sparse fossil or relict Recent distributions in the northwestern Pacifi c. This is in spite of tremendous diversifi cation throughout Atlantic and Pacifi c American waters. Here we analyze the morphologic variation of A. squamosa (Linneaus, 1758) from Thailand, focusing specifi cally on the correspondence between morphological variability and microhabitat variation, with the eventual goal of uncovering possible adaptive advantages of Anomalocardia relative to other chionine genera. Signifi cant variation was found among sites, characterized by differences in the shape of valve commissures and siphonal regions. The variation corresponds qualitatively with differences in sediment and water energy. We further compare A. squamosa to the congeneric, western Atlantic A. brasiliana (Gmelin, 1791), and the related eastern Pacifi c species, Iliochione subrugosa (Wood, 1828), establishing A. squamosa as a geographically widespread species, and fi nding all the taxa to be morphologically distinct. Finally, the analysis of A. brasiliana reveals that individuals from the Caribbean are morphologically distinct from Brazilian individuals.